PENGARUH RETURN ON ASSET (ROA) DAN DEBT TO EQUITY RATIO (DER) TERHADAP DEVIDEN PAYOUT RATIO (DPR) PADA PT JAPFA COMFEED INDONESIA Tbk PERIODE 2013-2022 - Sari, Fitriana Kartika; Amelia, Rizka Wahyuni (Journal of Research and Publication Innovation, 2024)
This research aims to determine Return On Assets (ROA) and Debt To Equity Ratio (DER) Against Dividend Payout Ratio (DPR) at PT Japfa Comfeed Indonesia Tbk 2013-2022. This method uses quantitative research, with a sample of financial reports in the form of panel data of 10 years. The analysis techniques used are descriptive statistical tests, classical assumption tests (normality test, multicollinearity test, heteroscedasticity test and autocorrelation test), simple linear regression analysis, linear regression analysis multiple, coefficient of determination test, hypothesis test (T test and F test) with the help of the IBM SPSS Statistics Version 27 program. The results of this research Return On Assets produced a Tcount value of -2.534, exceeding the Ttable value of 2.365 with a significance level of 0.039 < 0.050. Shows that the Return On Asset variable has a significant effect on the Dividend Payout Ratio. The Debt To Equity Ratio shows a T value of -3.332, above the table value of 2.365, with a significance level of 0.013 < 0.050. Shows that the Debt To Equity Ratio variable significantly influences the Dividend Payout Ratio. Return On Assets and Debt To Equity Ratio have a significant influence on the Dividend Payout Ratio. The F test obtained Fcount of 5.551, exceeding the Ftable of 4.74 and a significance level of 0.036 < 0.050. Then the results of the coefficient of determination test were 50.3%, the dependent variable Dividend Payout Ratio was influenced by the independent variables Return On Assets and Debt To Equity Ratio, while the remaining 49.7% was explained by other variables not examined in this research.